Impact of accounting standards in the credibility of financial reporting - Kemigisa Agnes (Uganda Christian university mukono, 2025)
The findings showed that compliance with accounting standards improved the transparency and accuracy of financial reports and helped strengthen investor confidence. At the same time, the study identified several challenges, including the complexity of IFRS, high implementation costs, limited staff expertise, and system constraints, which sometimes slowed down effective application. Overall, the study concluded that accounting standards play a key role in enhancing the credibility of financial reporting at Absa Bank Uganda Limited. It recommends ongoing staff training, greater investment in modern reporting systems, stronger regulatory follow-up, and improved internal controls. These recommendations are intended to help both the bank and regulators overcome the existing challenges. The study also adds to the limited research on IFRS adoption in developing countries, especially in the Ugandan banking sector.
The impact of accounting standards in the credibility of financial reporting
Undergraduate